The SQM/COSMO filter: reliable native pose identification based on the quantum-mechanical description of protein-ligand interactions and implicit COSMO solvation - Pecina, Adam; Meier, René; Fanfrlík, Jindřich; Lepšík, Martin; Řezáč, Jan; Hobza, Pavel; Baldauf, Carsten (Chemical communications (Cambridge, England), 2016)
Current virtual screening tools are fast, but reliable scoring is elusive. Here, we present the 'SQM/COSMO filter', a novel scoring function featuring a quantitative semiempirical quantum mechanical (SQM) description of all types of noncovalent interactions coupled with implicit COSMO solvation. We show unequivocally that it outperforms eight widely used scoring functions. The accuracy and chemical generality of the SQM/COSMO filter make it a perfect tool for late stages of virtual screening.